Systhesis and characterization of poly (N-vinyl pyrrolidon – co-vinyl acetate) - Thang, Tran Vu; Khoi, Nguyen Van; Thu Ha, Pham Thi; Cong, Trinh Duc; Phuong, Hoang Thi; Manh, Nguyen Van (Vietnam Journal of Science and Technology, 2014)
Copolymers of N-vinyl pyrrolidone (VP) and vinyl acetate (VA) were prepared by free radical polymerization in a solution of ethanol, using 2,2-azobisisobutyronitrile as an initiator. Properties of copolymers were characterized by spectrospcopic IR method, and also DSC and Gel permeation chromatography (GPC) analyses. Effect of temperature, monomer concentration and initiator concentration on monomer conversion into copolymer were studied. The monomer conversion into copolymer is highest at conditions: 700C reaction temperature, monomer concentration 40%, 1,5% initiator (w/w), after 250 minutes reaction